Hepatoprotective effects of celery in diethylene glycol induced toxicity in rats - Ekowati, Heny; Waluyo, Syaikah Syahidah; Endriastuti, Nialiana Endah (Faculty of Medicine, Universitas Trisakti, 2025)
Background Diethylene glycol (DEG) is a contaminant in pharmaceutical solvents and potentially induces hepatotoxicity. Celery is hepatoprotective due to its antioxidant properties. The objective of this study was to evaluate the hepatoprotective effects of celery on DEG-induced liver injury in rats. Methods An experimental laboratory study was conducted involving 25 male Wistar rats weighing 200 grams. They were randomized into five groups (5 rats in each group). Group A served as the control group, while Group B received oral administration of DEG at a dose of 3 g/kg BW twice daily for three days, following six days of food and water administration. The other three groups received DEG at 3 g/kg BW following six days of celery extract once daily administration of 100 mg/kg BW (C), 200 mg/kg BW (D), and 400 mg/kg BW (E). After 14 days, all rats were sacrificed. Observations were conducted macroscopically and microscopically using H&E staining. Liver damage was scored, Kruskal-Wallis followed by the Mann-Whitney was used to analyze the data. Results Macroscopic and microscopic examinations of the liver tissue in the celery groups revealed normal histological architecture with a significant reduction in liver damage. The ethanol extract of celery demonstrated hepatoprotective effects, as evidenced by a statistically significant reduction (p<0.05) in the activation of Kupffer cells, sinusoidal dilation, hepatocyte degeneration, and necrosis. Conclusion Celery has a protective effect against DEG-induced liver damage in rats based on the reduction in Kupffer cell activation, sinusoidal dilation, hepatocyte degeneration, and necrosis.